Ownership Structure, Debt Policy, and Financial Constraints - Bintang Lazuardi Benteng Buana Muslim; Abdul Moin (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2021)
This study aims to determine how the effect of ownership structure on debt policy with financial constraints as a moderating variable in non-financial companies listed on the Indonesia Stock Exchange in 2015-2019. The partial results of foreign, managerial, institutional, and family ownership do not affect the debt to equity ratio (DER). Financial constraints can moderate institutional ownership against the DER but cannot moderate foreign, managerial and family ownership to the DER. The partial results of foreign, managerial, institutional, and family ownership do not affect the debt to asset ratio (DAR). Financial constraints can moderate managerial and institutional ownership of the DAR but cannot moderate foreign and family ownership of the DAR. Meanwhile, foreign ownership, managerial, institutional, family, and financial constraints simultaneously influence debt policy.